Allergic contact dermatitis in psoriasis patients: typical, delayed, and non-interacting. - Maria Quaranta (Public Library of Science (PLoS), 2014)
Psoriasis is characterized by an apoptosis-resistant and metabolic active epidermis, while a hallmark for allergic contact dermatitis (ACD) is T cell-induced keratinocyte apoptosis. Here, we induced ACD reactions in psoriasis patients sensitized to nickel (n = 14) to investigate underlying mechanisms of psoriasis and ACD simultaneously. All patients developed a clinically and histologically typical dermatitis upon nickel challenge even in close proximity to pre-existing psoriasis plaques. However, the ACD reaction was delayed as compared to non-psoriatic patients, with a maximum intensity after 7 days. Whole genome expression analysis revealed alterations in numerous pathways related to metabolism and proliferation in non-involved skin of psoriasis patients as compared to non-psoriatic individuals, indicating that even in clinically non-involved skin of psoriasis patients molecular events opposing contact dermatitis may occur. Immunohistochemical comparison of ACD reactions as well as in vitro secretion analysis of lesional T cells showed a higher Th17 and neutrophilic migration as well as epidermal proliferation in psoriasis, while ACD reactions were dominated by cytotoxic CD8+ T cells and a Th2 signature. Based on these findings, we hypothesized an ACD reaction directly on top of a pre-existing psoriasis plaque might influence the clinical course of psoriasis. We observed a strong clinical inflammation with a mixed psoriasis and eczema phenotype in histology. Surprisingly, the initial psoriasis plaque was unaltered after self-limitation of the ACD reaction. We conclude that sensitized psoriasis patients develop a typical, but delayed ACD reaction which might be relevant for patch test evaluation in clinical practice. Psoriasis and ACD are driven by distinct and independent immune mechanisms.